Diabetes Educator: The Role and Experience in a Tertiary Government Hospital – A Technical Note (International Journal of Nursing Education, 2021)
Diabetes educator (DE) has a clear and important role in the overall management of patients with diabetes inall stages of care by providing much needed detailed information and support on adequate understanding ofthe pathology and safe-execution of the prescription by the specialist and other life-style changes to combatdiabetes effectively. This is more significant in countries like India where there is an unfavourable ratio ofphysicians to patients with diabetes. The accessibility of the health-care team by the huge number of patientswith diabetes in the government hospitals and consequent rush hours can be effectively compensated bythe DE by relieving the physician of routine and repeated individual counselling contributing to effectivephysician utilization and avoiding fatigue and burnout. Literature has evidence that this cost-effectiveintervention can improve patient outcome and warrants more investment in formal training and continuousacademic development of DEs. In this manuscript, a step-by-step counselling of patients with diabetes isdescribed for easy understanding and execution.
Keywords: diabetes educator, counselling of diabetes, self-management plan